Critical agency and glocal subjectivity in ELT material development: an analysis of English language textbook of Bangladesh - Khan, Harunur Rashid; Rahaman, Adilur (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper explores ‘glocal subjectivity’ in an English language textbook produced by National Curriculum and Textbook Board of Bangladesh for Grades XI-XII. In the era of globalization (Mukherjee & Krieckhaus 2011), glocal subjectivity, i.e. creation of self that appreciates the ingredients of both global and local spaces (Gutierrez 2013) is relevant for material development in ELT, as it carries implications for critical agency (Richmond 2011). In post-colonial countries, critical agency allows non-native textbook writers to exercise freedom in selecting themes and designing language learning activities which may be used in the classrooms to develop critical minds (Pineda-Báez 2004). Through qualitative content analysis (Julien 2008), this research examines how the non-native material writers in Bangladesh exerted critical agency to construct glocal subjectivity in the English textbook. Findings reveal that textbook writers constructed glocal subjectivity by selecting appropriate topics. Nevertheless, the textbook contains the following limitations: pedagogically unsound language learning activities, low aesthetic quality, misrepresentation of Bangladesh, and post-colonial ambivalence. Based on the findings, this paper suggests that textbook writers in the post-colonial countries need to be aware of the issue of representation and make use of the wisdom of Applied Linguistics to produce politically correct and pedagogically effective English language textbook.